1997
DOI: 10.1161/01.cir.96.8.2612
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Transition to Chronic Atrial Fibrillation in Patients With Paroxysmal Atrial Fibrillation by Signal- Averaged Electrocardiography

Abstract: These results indicate that P-SAE could be useful to identify patients at risk for the transition from PAF to CAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
3
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 16 publications
4
85
3
3
Order By: Relevance
“…Enlarged left atrial dimension was identified as a predictor of transition to persistent AF, as previously reported by Abe et al 13 Stretching of myocardial cells due to atrial dilatation may induce changes in electrical properties of atrial fibers that favor dispersion of refractoriness and disordered electrical activation and contribute to the persistence of AF. 19 Left atrial dimension was significantly greater in the group that did than in the group that did not develop persistent AF, but there were no significant differences between the two groups with respect to P-terminal force, an ECG indicator widely used for detecting left atrial dimension enlargement.…”
Section: Left Atrial Dimension On Ultrasonic Echocardiographysupporting
confidence: 73%
See 1 more Smart Citation
“…Enlarged left atrial dimension was identified as a predictor of transition to persistent AF, as previously reported by Abe et al 13 Stretching of myocardial cells due to atrial dilatation may induce changes in electrical properties of atrial fibers that favor dispersion of refractoriness and disordered electrical activation and contribute to the persistence of AF. 19 Left atrial dimension was significantly greater in the group that did than in the group that did not develop persistent AF, but there were no significant differences between the two groups with respect to P-terminal force, an ECG indicator widely used for detecting left atrial dimension enlargement.…”
Section: Left Atrial Dimension On Ultrasonic Echocardiographysupporting
confidence: 73%
“…8,10,11 The ability to predict progression from paroxysmal to persistent AF is therefore also important clinically. Previous studies have identified disease duration, 4 left ventricular dysfunction, 12 enlarged left atrial dimension, 13 advanced age, 14 prolongation of FPD, 13 and a low root mean square voltage for the last 30 ms of the filtered P wave 13 as indicators of transition from paroxysmal to persistent AF. How-72 Abbreviations: ECG = electrocardiogram, P-SAECG = P-wavetriggered signal-averaged electrocardiogram, FPD = filtered P-wave duration, RMS30 = root mean square voltage for the last 30 ms of filtered P-wave, Echo = echocardiogram, LAD = left atrial dimension, LVDd = left ventricular end-diastolic dimension, LVEF = left ventricular ejection fraction.…”
Section: Discussion Prediction Of Transition To Persistent Atrial Fibmentioning
confidence: 99%
“…4) Factors related to the development of permanent AF have been reported. 2,[5][6][7] A number of recent studies 3,[8][9][10][11] have associated AF and its treatment with quality-of-life issues.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, P-wave signalaveraged electrocardiography proved to be a noninvasive, low-cost, easily performed and reproducible method; therefore, it has been widely used in the evaluation and stratification of the risk of atrial fibrillation [16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%